DEEP STRUCTURE AND ORIGIN OF THE DZHIDA DEPRESSION OF THE EARLY CALEDONIDES - Altukhov Ye.N.; Gershanik S.Yu. (My University, 1989)
A key feature in present tectonic schemes for central Asia is the Dzhida structure of the early Caledonides. Its origin is explained by theories on both mobile, shifting and permanent, fixed continents, which, therefore, have different implications for metallogenic prediction. We accept the concept that the Dzhida depression is monogeosynclinal in structure and was formed by an 'asthenolithic' mechanism. The compiled starting density model of the Dzhida structure is supported by seismic exploration data and agrees well with the observed gravity field. Thus, metallogenic prediction models for the Dzhida area should be based on data on the geologic structure and history of this crustal segment alone. There are no grounds for extending them to adjacent regions, to the presumed roots and remnants of nappes.